2001
DOI: 10.1002/1615-9861(200101)1:1<108::aid-prot108>3.0.co;2-5
|View full text |Cite
|
Sign up to set email alerts
|

Towards defining the urinary proteome using liquid chromatography-tandem mass spectrometry II.Limitations of complex mixture analyses

Abstract: With an emphasis on obtaining a multitude of high quality tandem mass spectrometry spectra for protein identification, instrumental parameters are described for the liquid chromatography-tandem mass spectrometry analysis of trypsin digested unfractionated urine using a hybrid quadrupole-time-of-flight (Q-TOF) mass spectrometer. Precursor acquisition rates of up to 20 distinct precursors/minute in a single analysis were obtained through the use of parallel precursor selection (four precursors/survey period) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
71
0

Year Published

2001
2001
2007
2007

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 126 publications
(72 citation statements)
references
References 7 publications
1
71
0
Order By: Relevance
“…Several research teams have worked on profiling the healthy human urine proteome using electrophoresis and/or liquid chromatography followed by mass spectrometry identification (1)(2)(3)(4)(5).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Several research teams have worked on profiling the healthy human urine proteome using electrophoresis and/or liquid chromatography followed by mass spectrometry identification (1)(2)(3)(4)(5).…”
mentioning
confidence: 99%
“…Even for the other 83 proteins identified by single peptide with multiple hits, the reliability was still more than 97%. 94 proteins were identified in previous urine proteome studies (1)(2)(3)(4)(5). 43 proteins were also identified in serum Nglycoproteome (11)(12)(13).…”
mentioning
confidence: 99%
“…It is likely that many more spectra could be assigned to each of these classes of chemical modifications with more extended searching, and there are undoubtedly additional classes of chemical modifications yet to be discovered. We conclude from these studies that in most cases these additional identifications do not add to the number of distinct peptides or proteins that can be identified, and may even eliminate borderline identifications by providing alternative explanations (21). We found that relatively few unmodified CICAT peptides were eliminated by this means.…”
Section: Discussionmentioning
confidence: 99%
“…In this report, the ChemScore of the b(n-1)Ď©18 ion is counted the same as an ordinary b ion (Table I, rule 21).…”
Section: Spectrum Classificationmentioning
confidence: 99%
“…The algorithms will therefore fail to find a correct answer if the sample peptide differs from a canonical version in a database due to mutations, posttranslational modifications (PTMs) or database sequence errors, because the calculated mass from the database sequence may no longer match the measured mass. A list of peptide candidates that do not include the correct peptide will provide incorrect answers [3]. To overcome this drawback, an exhaustive search approach was suggested [4] where a virtual database of all modified peptides from a small set of potential modifications is generated and experimental spectra are matched against this enlarged database.…”
Section: Introductionmentioning
confidence: 99%